Facial carbuncle – a new method of conservative surgical management plus irrigation with antibiotic-containing solution. Issue 9 (17th April 2017) - Ngui, L X; Wong, L S; Shashi, G; Abu Bakar, M N
Abstract: Objective: This paper reports on a non-conventional method for the management of facial carbuncles, highlighting its superiority over conventional surgical treatment in terms of cosmetic outcome and shorter duration of wound healing. Background: The mainstay of treatment for carbuncles involves the early administration of antibiotics in combination with surgical intervention. The conventional saucerisation, or incision and drainage, under normal circumstances results in moderate to large wounds, which may need secondary surgery such as skin grafting, resulting in a longer duration of wound healing and jeopardising cosmetic outcome. Case reports: The reported three cases presented with extensive carbuncles over the chin, face and lips region. In addition to early commencement of intravenous antibiotics, the pus was drained, with minimal incision and conservative wound debridement, with the aim of maximal skin conservation. This was followed by thrice-daily irrigation with antibiotic-containing solution for a minimum of 2 consecutive days. The wounds healed within two to four weeks, without major cosmetic compromise. Conclusion: The new method showed superior cosmetic outcomes, with a shorter duration of wound healing. Conservative surgical management can be performed under regional anaesthesia, which may reduce morbidity and mortality; patients with facial carbuncles often have higher risks with general anaesthesia.